2021
DOI: 10.1371/journal.pone.0256893
|View full text |Cite
|
Sign up to set email alerts
|

The different outcomes between breast-conserving surgery plus radiotherapy and mastectomy in metaplastic breast cancer: A population-based study

Abstract: Background Metaplastic breast cancer (MBC) are rare. The survival outcomes of MBC patients after breast conserving surgery plus radiotherapy (BCS+RT) or mastectomy have not been established. The study aimed to compare survival outcomes of MBC patients subjected to BCS+RT or mastectomy therapeutic options. Methods Patients who were subjected to BCS+RT or mastectomy between 2004 and 2014 were enrolled in this study through the Surveillance, Epidemiology and End Results (SEER) database. Breast cancer-specific s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Previous research has demonstrated that MBC patients who undergo breast-conserving surgery plus radiotherapy exhibit a better prognosis than those who undergo mastectomy alone. 8 , 9 Evidence has also suggested that chemotherapy is associated with improved prognosis. 5 , 10 Meanwhile, most current studies agree on the important role of radiotherapy in improving prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that MBC patients who undergo breast-conserving surgery plus radiotherapy exhibit a better prognosis than those who undergo mastectomy alone. 8 , 9 Evidence has also suggested that chemotherapy is associated with improved prognosis. 5 , 10 Meanwhile, most current studies agree on the important role of radiotherapy in improving prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the oncological safety of breast-conserving surgery (BCS) plus radiotherapy compared to mastectomy for early BC treatment has been largely confirmed, from historical trials until more recent studies (Magnoni et al, 2022b). In addition, recently updated guidelines have highlighted that BCS followed by radiotherapy should be discussed for nonmetastatic BRCA mutated BC patients, if considerate appropriate after multidisciplinary discussion (Corso and Magnoni, 2021b) When mentioned, the available major series (Leyrer et al, 2017;Corso et al, 2021a,b) on MpBC have considered clear margins for invasive breast carcinoma and BCS followed by radiotherapy resulted as safe as mastectomy (Corso et al, 2021a;Xia et al, 2021;Wang et al, 2022a,b).…”
Section: Surgery Breast Surgerymentioning
confidence: 98%
“…Moreover, a propensity score-matched analysis of 1197 MpBC patients showed that patients receiving BCS followed by radiotherapy had higher OS than those receiving mastectomy (Xia et al ., 2021). A total of 2412 MpBC patients were also studied with a median follow-up of 73 months.…”
Section: Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Until 1997, the American Joint Committee on Cancer (AJCC) defined DCIS-Mi as a tumor with an area of invasion less than or equal to 1 mm as T1mic in the TNM staging system [7,8]. Nowadays, it is most widely accepted as DCIS with an area of focal invasion 1 mm or less in diameter by the majority of pathologists and clinicians [9,10]. According to the definition of DCIS-Mi, It is important to distinguish DCIS-Mi from another premalignant and malignant breast lesions, such as DCIS and invasive breast cancer.…”
Section: Definition and Clinicopathological Characteristics Of Dcis-mimentioning
confidence: 99%